Syringe Solid-Phase Extraction for Cu(II) in Powder Milk Using Alginate-Chitosan-PVA Adsorbents: Method Development and Application - Yaqin, Ahmad Akhib Ainul; Siswanta, Dwi; Suherman, Suherman (Universitas Gadjah Mada, 2026)
This research designed and optimized a syringe solid-phase extraction (SPE) technique employing a modified chitosan, alginate, and PVA (CAP) adsorbent for the determination and preconcentration of Cu(II) ions in powdered milk samples. The material was characterized using FTIR, SEM-EDX, and XPS analyses, which confirmed the detection of predominant –COOH, –NH2, and –OH functional groups. Optimization of the method was performed using both the one-variable-at-a-time (OVAT) approach and the central composite design (CCD) method. Parameters such as pH, CAP dosage, number of samples, and eluent (including HNO3) were evaluated. Optimal OVAT conditions were pH 4.0, 100 mg CAP, 5 samples, and eluent cycles with 2.0 M HNO3, achieving a 100-fold preconcentration. CCD optimization yielded similar results, with slight variations: optimal pH 4.3, CAP mass 105 mg, and 5 eluent cycles with 2.0 M HNO3. CAP exhibited high selectivity (90–99%) and was reusable for up to three adsorption–desorption cycles. Validation using reference material (ERM–BD151) resulted in a recovery of 95.4% for Cu(II). Application of the validated method to real milk samples yielded recoveries of 90.8–97.8%, demonstrating high accuracy. These findings suggest that syringe SPE using CAP is an efficient technique for Cu(II) preconcentration in food matrices.